Welfare that work tests : a thesis submitted to fulfil the requirements of the degree of Master of Arts (Social Policy), Massey University - Barker, Sarah (Massey University, 2000)
This thesis is a critical analysis of the work test policy which is central to current income support policy. The study traces the discourse within welfare theory and policy, which relate to the principles and conditions under which benefits are provided to the unemployed, and other work tested beneficiaries. Definitions of 'deserving' and 'undeserving', 'employment' and 'unemployment', and 'benefit dependency' and 'self - sufficiency' are argued to be embedded within these theoretical discourses, which produce social policy prescriptions that correspond with these theoretical definitions. It is argued that the employment effects of the work test are insignificant and that in reality, its overall purpose is to promote ideology which seeks to 'remoralise' welfare by requiring that work tested beneficiaries behave in a particular way. The research is based on a survey and discursive interviews of a small group of work tested beneficiaries, and it was intended to establish their experiences and perceptions of the work testing process. The data identifies that the work test policy is significant to beneficiaries insofar as they have no choice about how it is imposed upon them. They are only able to choose between retaining the benefit by complying, or losing the benefit by failing to comply. The data also identifies that the work test is fairly vigilantly administered, and it is argued that this factor detracts from any employment focus that is ostensibly held to be one of the main objectives of the policy. It is suggested that a shift in income support policy and labour market policy is required which encompasses new definitions of employment and unemployment, and which can serve to remove the traditional stigma attached by society to individuals who are welfare beneficiaries.
Keywords: Income maintenance programmes; Work testing; Work-tested welfare; Unemployment benefits